Pengendalian Proses Pengolahan Air Limbah Dengan Menggunakan Lumpur Aktif - Hendartini Hendartini (Jurnal Kimia dan Kemasan, 1998)
One of the most effective way to remove the pollutant in waste water is biological treatment. There are several different systems used to get the mikroorganism to do their jobs. Such as : activated sludge, biological filters, and ponds. Activated sludge is the one that widely use in many plants over the world. To have the best result we have to know how to control the mikroorganism 's life that we can get from the experience.